Influence of genotype and developmental stage on plant dry matter distribution and shootroot ratio in banana and plantain - Blomme, Guy; Teugels, K.; Swennen, Rony L.; Tenkouano, A. (2005)
Detailed time studies on the distribution of dry matter within a Musa spp. plants ' root and shoot system have not been done. Hence, the influence of genotype and developmental stage on the root system development, plant dry matter distribution and the shoot-root ratio of field grown Musa spp. plants was assessed in this study. Experiments were done at the International Institute of Tropical Agriculture Onne High Rainfall station, Nigeria in an ultisol soil. Plants were assessed at four weekly intervals for the diploid 'Calcutta 4' (Musa AA group) and the plantain 'Mbi Egome' (Musa AAB group). The 'Calcutta 4' plants were in vitro-derived, while the 'Mbi Egome' plants were sucker-derived. In addition, shoot-root dry matter ratio was assessed at flower emergence for seven Musa spp. genotypes including the dessert banana 'Valery' (Musa AAA group), the plantains' Agbagba ' and' Obino l'Ewai' (Musa AAB group), the cooking banana 'Cardaba' (Musa ABB group) and the plantain tetraploid hybrids 'TMPx548-9', 'TMP x 1658-4' and 'TMPx5511-2' (Musa group AAB x AA). There was an effect of type of planting material on the shoot-root ratio of plants in the vegetative stage. For example, juvenile in vitro-derived 'Calcutta 4' plants allocated up to 45% of dry matter to the root system. In contrast, less than 20% of plant dry matter was allocated to the roots of juvenile sucker-derived 'Mbi Egome' plants, while the corm contained up to 70% of plant dry matter. At flower emergence of the plant crop, the shoot portion of the mat (i.e. mother plant and lateral shoots) accounted for approximately 90% of the total dry matter. Thus, evaluation of the shoot-root ratio between similar genotypes should be done at the same morphogenetic age. In addition, variation in shoot-root ratio of the plant crop at flower emergence was observed between genotypes and within Musa groups. However, less variation in the shoot-root ratio was observed for the whole mat at flower emergence of the plant crop, indicating that there was a similar partitioning of dry matter between the mat shoot and root system for the Musa spp. landraces and hybrids. Breeding for a decreased mat shoot-root ratio, under similar environmental conditions, to enhance nutrient and water uptake and plant anchorage may thus be difficult